Development of the Wind Tunnel CFD Model for Clarifying Rotor Blade Airfoil Unsteady Aerodynamic Researches - Oleg E. Kirillov (TEM Journal, 2021)
A computational model of a wind tunnel (WT) with a special experimental rig has been developed directly for studying unsteady aerodynamic characteristics of a wing section with a helicopter blade profile. The model was constructed using CFD (Computational Fluid Dynamics) methods based on the URANS approach (Unsteady Reynolds Averaged Navier Strokes Equations). Therefore, the aerodynamic characteristics of the airfoil can be determined, taking into account influence of the WT walls such as walls perforation and various configurations of the experimental rig. Simulation of the flow around the wing section with the SC1095 airfoil in steady and unsteady settings is performed. The flow features in the working section of the WT and the experimental rig are analyzed. For a particular case, the calculation method was validated in a 2D formulation on the basis of available experimental data. The developed model can be used to refine the methods of processing experimental data, taking into account the individual characteristics of the WT and the experimental rig configuration.